2019
DOI: 10.3126/nmj.v2i2.26007
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of Sleep Disorders and Chronic Respiratory Diseases: An Emerging Health Dilemma

Abstract: Introduction: The burden of Overlap Syndrome (coexistence of sleep-related breathing disorders in patients with respiratory diseases) is high in developing countries, and such a phenomenon implies higher morbidity. The study was conducted to measure the prevalence of sleep-related breathing disorders in patients with Respiratory Symptom Complex and to identify factors associated with the severity of sleep-related breathing disorders.Materials and Methods: A hospital-based cross-sectional study of 50 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Reporting included presence of pulmonary arterial hypertension 30 and cor pulmonale. 29 , 30 , 35 , 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reporting included presence of pulmonary arterial hypertension 30 and cor pulmonale. 29 , 30 , 35 , 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
“…One was published in the 1980s, 29 7 between 2000 and 2010, 30 36 and 19 after 2011. 20,37 54 All included studies were cross-sectional, direct observations of clinical notes, comparative and single point survey designs. 20,29 54 The studies reported on diseases (usually self-reported), symptoms, related health conditions and lung function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations